Gastronomy Tourism Management on Nakhon Sawan District Nakhon Sawan Province - Jaipeng, Chanistha; Sitsirat, Jureerat (Journal of Human and Society, Sisaket Rajabhat University, 2022)
This research has the objective for 1) to study the satisfaction of tourists in the Gastronomy Tourism on the readiness in accessing to the tourist attraction convenient, the convenient facilities and the good management. and; 2) to determine the guidelines of the Gastronomy Tourism in Mueang Nakhon Sawan District, Nakhon Sawan Province to create the sustainability. The researcher used the Quantitative Research. To gather the information by using questionnaires. The research sample of the research are, the tourists that travelled to use the service of restaurant in total of 500 persons. To analyze with the descriptive statistics. This will show about the frequency value, the percentage value, the average and the standard deviation. The result of research found out that; 1) the respondent of the questionnaires has the satisfaction in the good management of the restaurant in the most level. While the readiness in accessing to the tourist attraction and facilities, the respondent of questionnaires has the satisfactory in the medium level due to some of the restaurants are difficult to be accessed and there is the limitation in the parking area. The findings of the study are reflected in the Gastronomy Tourism in Mueang Nakhon Sawan District, is not ready and doesn’t have enough capacity. Nakhon Sawan Province has a reputation on food but it still not the main city to attracted the tourists. 2) the guideline in the Gastronomy Tourism Management in Mueang Nakhon Sawan District should held a meeting together, to consult and find the guideline in setting the activity to contribute to tourism being the stimulation to create repeat trips and word of mouth, including having the connection of the tourist attraction, the restaurant, the accommodation, and the souvenir shop, as well as contributing to Nakhon Sawan becoming a tourist destination in the future.